Pengaruh Moral Ekonomi dan Kewirausahaan Nelayan Terhadap Perilaku Ekonomi Rumah Tangga Nelayan di Pantai Kenjeran Surabaya Jawa Timur - Andjarwati, Tri (JMM17 : Jurnal Ilmu ekonomi dan manajemen, 2017)
Kenjeran Beach in Surabaya is one of the areas that has potential in the sector of fishery is large enough. Fisheries on the coast of Kenjeran Surabaya include marine fisheries, public waters. Therefore the utilization of fish resources optimized rationally so as to improve the welfare for the fishermen's income. This study talks about the Effect of Economic Morale and Degree of Entrepreneurship on Fisherman Household Economic Behavior at Kenjeran Beach Surabaya East Java. The population of this research is 624 fishermen in Kenjeran Surabaya The determination of the number of samples based on a simple random method with Slovin formula with dispersion of 5% resulted in a total sample of 244 people From the results of model testing in this study, with estimation of Generalized Least Square Estimation (GLS), structural equation model analysis (SEM), proportional random sampling method and software assistance Amos 22, on 244 respondents. The results showed that: 1). Economic morals affect the degree of entrepreneurship of fishermen in Kenjeran Surabaya. 2). Economic morals affect the behavior of fishermen economy in Kenjeran Surabaya. 3). The fisherman entrepreneurship significantly influences the behavior of fishermen economy in Kenjeran Surabaya. 4). Economic morals have an indirect effect on economic behavior through fishing entrepreneurship in Kenjeran Surabaya. Key words: Moral economy of fisherman, entrepreneurship of fisherman, economic behavior